2021
DOI: 10.3390/rs13050986
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Method for Dynamic Wave-Related Errors of Interferometric SAR Ocean Altimetry under Multiple Sea States

Abstract: The spaceborne interferometric synthetic aperture radar (InSAR) is expected to measure the sea surface height (SSH) with high accuracy over a wide swath. Since centimeter-level accuracy is required to monitor the ocean sub-mesoscale dynamics, the high accuracy implies that the altimetric errors should be totally understood and strictly controlled. However, for the dynamic waves, they move randomly all the time, and this will lead to significant altimetric errors. This study proposes an analytical method for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…The significant factors affecting the inversion of the ocean waves are velocity bunching and the layover effect, sea surface morphology, and the payload performance. In this respect, Chen et al, (2021) [45] analyzed the altimetric accuracy of the X, Ku, and Ka bands under different sea states based on numerical simulations. The experimental results demonstrated that the dynamic wave-related errors of the InSAR altimetry were not sensitive to the frequencies but to the sea states.…”
Section: Discussionmentioning
confidence: 99%
“…The significant factors affecting the inversion of the ocean waves are velocity bunching and the layover effect, sea surface morphology, and the payload performance. In this respect, Chen et al, (2021) [45] analyzed the altimetric accuracy of the X, Ku, and Ka bands under different sea states based on numerical simulations. The experimental results demonstrated that the dynamic wave-related errors of the InSAR altimetry were not sensitive to the frequencies but to the sea states.…”
Section: Discussionmentioning
confidence: 99%
“…In high sea state 2, wind direction (180 degrees) is parallel to range direction, the SSH fluctuation caused by the background sea wave fluctuates greatly along the range direction. From the research [10] it can recognize that the random movement of the sea surface will cause the target point to shift in the azimuth and range directions in the SAR image, which is the main factor causing the height measurement error, while the range direction shift will have a great impact on the height measurement error. Therefore, when the radar look-directions are parallel to the wind direction, the height measurement error will increase significantly.…”
Section: Rangementioning
confidence: 99%
“…However, multi-source errors of wide-swath altimetry, including random noise (RN), baseline roll and length errors, dry and wet troposphere delay, and sea state bias (Ren et al, 2020), will directly limit the precision of the retrieved SSH data. As a result, one of the most critical studies on the wide-swath altimetry mission is how to reduce the SSH errors (Chen et al, 2021), and for each error source, specific reduction methods should be developed according to the corresponding error model. On this basis, this study focuses on the research of SSH errors associated with baselines, involving height error associated with the both baseline roll (HEBR) and baseline length (HEBL).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this method inevitably generates the leakage of SSH signals, whereas the other three methods can only be applied to reduce local errors, and the residual errors are related with the variation of ocean topography during the time interval of two crossovers or overlap passes (Dibarboure and Ubelmann, 2014). Moreover, the ocean topography must be various (Chen et al, 2021). When the interval time of two passes is longer than three days, the difference between these two passes will influence the reduction results (Dibarboure et al, 2012;Dibarboure and Ubelmann, 2014).…”
Section: Introductionmentioning
confidence: 99%